Mecanismos de terror de Estado en el caso de los niños perdidos del franquismo: historia y nueva novela histórica - Wachowska, Judyta (Studia Romanica Posnaniensia, 2015)
The purpose of this paper is to uncover the mechanisms used by the Francoist regime to seize the children of its political opponents, as well as to discuss the problem as depicted in contemporary historical novels. In order to achieve these goals, the paper begins with an inquiry into eugenics, as interpreted by the infamous Spanish psychiatrist Antonio Vallejo Nágera. Further, the author reviews the processes through which biological parents (and/or family) lost the legal control over their children, many of whom had their identities changed. Consequently, the analysis focuses on three new historical novels (La voz dormida by Dulce Chacón, Mala gente que camina by Benjamin Prado, and Si a los tres años no he vuelto by Any R. Cañil), which use the mediation of historical memory to recover the remembrance of the lost children of the Francoist regime.